MOTIVASI IBU RUMAH TANGGA YANG BEKERJA DI DESA RANAH KECAMATAN KAMPAR KABUPATEN KAMPAR - Rahma, Gustina Baiti; Kadarisman, Yoskar (Jurnal Ilmiah Dikdaya, 2025)
The work status of housewives is also classified into two, namely working housewives and non-working housewives. A working housewife is a woman who uses her time not only to manage the household but also has roles outside the household, with the aim of earning income that can be used for family needs. There are several professions that working housewives undertake, such as opening a business both at home and outside the home and also working in offices. A working housewife is a mother who has a role in professional activities (work) such as business and office activities. A working mother has her own reasons for choosing to carry out her dual role. Apart from wanting to have a career and develop her potential, a mother plays a dual role because she wants to help her husband in meeting his daily needs. Some working mothers carry out dual roles because they feel bored when they are at home and do not do activities that can reduce boredom.